Neuroectodermal (CHIME) syndrome: an additional case with long term follow up of all reported cases. Issue 6 (June 1995) - Shashi, V; Zunich, J; Kelly, T E; Fryburg, J S
Abstract : A new neuroectodermal syndrome (designated CHIME syndrome) was described in 1983 with a total of four patients reported, it is presumed to be an autosomal recessive disorder because of recurrence in sibs. The main features include ocular colobomas, congenital heart disease, early onset migratory ichthyosiform dermatosis, mental retardation, conductive hearing loss, seizures, and typical facial features. We report a fifth child with the condition, confirming the unique nature of the condition. Long term follow up information on this patient, as well as the previously described cases, provides information regarding the outcome for these patients, which includes general good health, severe mental retardation, seizures that worsen after puberty, conductive hearing loss, and chronic migratory ichthyosiform skin rash without scarring.